2014
DOI: 10.1007/s00467-014-2873-9
|View full text |Cite
|
Sign up to set email alerts
|

Acidosis: progression of chronic kidney disease and quality of life

Abstract: Metabolic acidosis (MA) is relatively common in patients with chronic kidney disease (CKD) particularly in stages 4 and 5. It is assumed to play a contributory role in the development of several complications including bone disease, skeletal muscle wasting, altered protein synthesis, and degradation. Recent evidence also suggests that even mild acidosis might play a role in progressive glomerular filtration rate loss. Experimental and clinical studies suggest that correction of acidosis by alkali therapy atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…It is known that metabolic acidosis in people with chronic renal failure can lead to muscle wasting and correction of the acidosis can mitigate the muscle loss [20]. This effect of acidosis on muscle may contribute to the diminished weight gain observed in people on KD.…”
Section: Acidosis-related Adverse Effects Of Ketogenic Dietmentioning
confidence: 99%
“…It is known that metabolic acidosis in people with chronic renal failure can lead to muscle wasting and correction of the acidosis can mitigate the muscle loss [20]. This effect of acidosis on muscle may contribute to the diminished weight gain observed in people on KD.…”
Section: Acidosis-related Adverse Effects Of Ketogenic Dietmentioning
confidence: 99%
“…Our research question will be linked to the recent evidence that alkali therapy also slows the progression of CKD [32,33]. To this end, the clinical trial will include 3 arms, namely, placebo, potassium chloride, and potassium citrate.…”
Section: Introductionmentioning
confidence: 99%
“…A recent retrospective study has evidenced that MA is also associated with increased risk of graft loss and patient mortality in kidney transplant recipients [ 19 ]. Although several studies have demonstrated a beneficial role for alkali therapy on the progression of CKD [ 5 , 7 , 11 15 ], no data is available if alkali treatment may also allow to better preserve renal allograft function in kidney transplant recipients with metabolic acidosis.…”
Section: Discussionmentioning
confidence: 99%
“…These data could be confirmed by other authors [ 9 ] and similar to CKD patients creatinine clearance was markedly lower in the group of transplant patients with MA compared to the non-acidotic patients. Over the past few years several studies have shown that MA plays an important role in the progression of CKD and that low serum bicarbonate levels are associated with a higher risk of progressing to end-stage renal disease [ 5 , 7 , 11 15 ]. Amelioration of MA in CKD patients with alkalinizing therapies delayed progression of GFR loss [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%